Effect of Poster and KIA Book Education on Mothers’ Knowledge of Father Involvement in Toddler Development - Nina Pamela Sari; Anisa Nuroftavia (Asy-Syifa : Journal of Science and Technology Nursing, 2026)
Purpose: The purpose of this study is to determine the effect of health education using poster media and the Mother and Child Health (KIA) Book on mothers’ knowledge regarding father involvement in supporting the growth and development of toddlers. Methods: This study employed a pre-experimental design with a one-group pretest–posttest approach. The subjects consisted of 63 mothers with toddlers in Kersamenak Village, Kawalu District, Tasikmalaya City, selected using a purposive sampling technique. Health education was delivered through poster media and the KIA Book, focusing on the role of fathers in childcare and child development. Data were collected using a questionnaire to measure mothers’ knowledge before and after the intervention.  Results: The results showed a significant improvement in mothers’ knowledge after the health education intervention. The average knowledge score increased following the intervention. Statistical analysis revealed a p-value of 0.000 (p < 0.05), indicating a significant effect of health education using poster media and the KIA Book on improving mothers’ knowledge regarding father involvement in toddler growth and development. Conclusions: Health education using poster media and the KIA Book is effective in increasing mothers’ knowledge about the role of fathers in supporting child growth and development. Therefore, continuous implementation of this intervention is recommended in posyandu activities and community health center programs to strengthen family involvement in optimizing child development.